Addendum to 4, 4'‐Methylene diphenyl diisocyanate (inhalable fraction)[BAT Value Documentation, 2007]. Issue 2 (27th April 2016) - Leng, G.; Reuter, U.; Drexler, H.; Hartwig, A.; ,
4, 4'‐Methylene diphenyl diisocyanate(MDI) (inhalable fraction) (14. Lieferung 2007): The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated 4, 4'‐Methylene diphenyl diisocyanate (MDI) (inhalable fraction) in 2006. The Commission established a "Biologischer Leitwert" (BLW), which allows for a threshold value in spite of insufficient data in order to make use of the advantage of biological monitoring. The provisional BAT value to date was based on the relationship between external and internal exposure and was creatinine‐related. For an MDI concentration of 50 µg/m3, a urinary excretion of MDA of no more than 10 μg/g creatinine was obtained (Lewalter and Steinmann‐Steiner‐Haldenstätt 1994). The correlation is based on excretion data that are volume‐related, not creatinine‐related. Taking recent data from MDI monitoring, also from occupational medical sources, into account, a BLW ("Biologischer Leitwert") of 10 μg 4, 4'‐diaminodiphenylmethane (MDA) (after hydrolysis)/l urine is established. Sampling should be carried out at the end of exposure or the end of the shift.